REVITALISASI KEARIFAN LOKAL DI ACEH: Peran Budaya dalam Menyelesaikan Konflik Masyarakat - Nurdin, Abidin (Analisis: Jurnal Studi Keislaman, 2013)
This article studies on revitalization of local wisdom Aceh society in solving of conflict. When conflicts and cases appear, it’s solved by  using  tradition  and  culture  approach  that  known  as  di’et, sayam, suloh, peusijuk  and peumat jaroe. Those  local wisdoms valued strongly as spirit of Islam so that it’s still survive and still applicated in society. Impact of conflict usually such death, bodily harm and physical defect. Process of conflict resolution, generally solved  in gampong  by involving  of geuchik,teungku  imum  and personage   of  tradition.   Conflict   resolution   valued  effectivly enaough and succes. So that,  Goverment  of Aceh made Canoon (qanun) to revitalize  local wisdom by revitalization several adat institutions that’s  not running well for nowdays.Using  of local wisdom,  explain  that  cultural  approach  is  successfull  and  has many superiority such as; cheap of coast, fast, flexibel and last but not least keeping of brotherhood if it compared when the conflict solved in the court that expensiv coast, long time, unflexible and usually breaking of brotherhood.